Egocentric distance perception in older adults: Results from a functional magnetic resonance imaging and driving simulator study - Eudave, Luis; Martínez, Martín; Luis, Elkin O.; Pastor, María A. (Frontiers in Aging Neuroscience, 2022)
The ability to appropriately perceive distances in activities of daily living such as driving is necessary when performing complex maneuvers. With aging, certain driving behaviors and cognitive functions change, however, it remains unknown if egocentric distance perception (EDP) performance is altered and whether its neural activity also changes as we grow older. To that end, nineteen young and seventeen older healthy adults drove in a driving simulator and performed an fMRI experiment where we presented adults with an EDP task. We discovered that: a) EDP task performance is similar between groups, with higher response times in older adults; b) older adults show higher prefrontal and parietal activation, as well as c) higher functional connectivity within frontal and parietal-occipital-cerebellar networks; and d) an association between EDP performance and hard braking behaviors in the driving simulator was found. In conclusion, EDP functioning remains largely intact with aging, possibly due to an extended and effective rearrangement in functional brain resources and may play a role in braking behaviors while driving.